2022
DOI: 10.1002/edm2.397
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of neutrophil‐to‐lymphocyte ratio for atrial fibrillation and stroke in type 2 diabetes mellitus: The Hong Kong Diabetes Study

Abstract: Introduction:Neutrophil-to-lymphocyte ratio (NLR) is a routinely available biomarker that reflects systemic inflammation. The study evaluated the predictive value of NLR for ischemic stroke and atrial fibrillation (AF) in patients with type 2 diabetes mellitus. Methods:This was a population-based cohort study of patients with type 2 diabetes mellitus and complete blood count tests at baseline between 1 January 1st, 2009, and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…The utility of traditional biomarkers like estimation of blood glucose and HbA1c to manage T2DM appears to be limited. This is evident from the reports that suggest the potential application of NLR to manage T2DM and predict long-term complications like stroke and kidney and cardiovascular diseases, among others [20,21].…”
Section: Discussionmentioning
confidence: 94%
“…The utility of traditional biomarkers like estimation of blood glucose and HbA1c to manage T2DM appears to be limited. This is evident from the reports that suggest the potential application of NLR to manage T2DM and predict long-term complications like stroke and kidney and cardiovascular diseases, among others [20,21].…”
Section: Discussionmentioning
confidence: 94%
“…Our AI-enhanced diabetes model complement previously published, Chinese-specific diabetes CVD risk models by other groups 45,46 . Our future model will also capture fluctuations in inflammation using biomarkers 47 . Finally, we are developing cancer-specific CVD risk models based on our recent publications 48 , most notably our series on prostate cancer 49-53 .…”
Section: Discussionmentioning
confidence: 99%
“…Patients of this study have been identified from the Clinical Data Analysis and Reporting System (CDARS), which centralizes information on patients from individual local hospitals to establish comprehensive medical data throughout the Hong Kong. The system has been previously utilized by multiple teams to conduct population-based cohort studies [21][22][23][24], including those focused on diabetes [25]. All pertinent data including clinical characteristics, disease diagnoses, laboratory results and drug treatment details based on the population in Hong Kong can be extracted from this system.…”
Section: Methods Study Design and Populationmentioning
confidence: 99%